Pengaruh Kualitas Produk, Harga dan Citra Merek Honda Terhadap Loyalitas Pelanggan Pada Bengkel Honda Ahass Dirawalumbu - Maharani, Putri Octavia; Ali, Hapzi; Khan, Muhammad Asif (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Previous research or related research and previous theoretical studies are very significant for research or scientific articles. Relevant and interrelated previous research plays a role in supporting the theory and the relationship or influence between variables. This article reviews the influence of product quality, price and brand image on customer loyalty at the Honda AHASS workshop in Rawalumbu. This article is a study of management literature. Marketing aims to build a hypothesis that can be used in further research. The implementation of this literature review article is as follows: 1) Product quality influences customer loyalty; 2) Price affects customer loyalty; 3) Brand Image influences Customer Loyalty.